THE EFFECT OF ADVERTISING ON TELEVISION MEDIA, REPUTATION, INFORMATION QUALITY ON PURCHASE INTEREST IN TOKOPEDIA (STUDY ON TOKOPEDIA CONSUMERS IN TEBING HIGH) - Sri Winda Hardiyanti Damanik; Fitrianingsih; Sarwoto; Indah Permata Sari (CV. Radja Publika, 2023)
The television media advertising variable (X1) has a positive and significant effect on the purchase intention variable (Y) for Tokopedia consumers in Tebing Tinggi. This means that television media advertising is one of the determining factors that influence consumer buying interest. the better the television media advertising used by the company, the more interest in buying it will increase in consumers. The reputation variable (X2) has a positive and significant effect on the purchase intention variable (Y) for Tokopedia consumers in Tebing Tinggi. This means that reputation is one of the determining factors that influence consumer buying interest. The better the company's reputation, the more consumers' buying interest will increase. The information quality variable (X3) has no effect on the buying interest variable (Y) for Tokopedia consumers in Tebing Tinggi. This means that the quality of information is not the main factor that determines consumer buying interest. Information quality is not a variable that influences the level of consumer buying interest. Television media advertising variables (X1), reputation (X2) and quality of information (X3) simultaneously influence purchase intention (Y) among Tokopedia consumers in Tebing Tinggi. meaning that if advertisements on television media, reputation, quality of information get better then consumer buying interest will be higher and this applies if the three independent variables are good/high.